Berg Balance Test (Bbt) and Time Up and Go Tes (Tugt) as Falls Prediction on Elderly - Nursalam Nursalam; Retno Indarwati; Mikhael Caraka Kristi (Jurnal Ners, 2008)
Introduction: Aging process represent the natural process which cannot obtivated. It caused by biological factor that goes naturaly and continuously that influence the anatomical, biochemical and physiological change. The natural change in this aspect giving contribution of falling on elderly. The objective of this study was to compare falls prediction on elderly using Berg Balance Test and Time Up and Go Test. Method: Design used in this study was comparative study design. The population was 28 elderly. Total sample was 20 elderly enrolled by means of purposive sampling, taken according to inclusion criteria. The independent variabels were Berg Balance Test and Time Up and Go Test The dependent variabels were falls prediction, falls, and falls influence factors. Data were colected using Berg Balance Test, Time Up and Go Test and questionnaire that modify from Minnesota Safety Council  Fall Prevention Checklist.  Data were then analyzed using kruskall-wallis test and mann-withney test with level of significance α≤0.05. Result: The result showed that Berg Balance Test (BBT) and Time Up and Go test (TUGT) had differences falls prediction with significance level of  p=0.014. :The  dominant factors that caused of falls was gait. Time Up and Go Test (TUGT) has valid prediction than Berg Balance Test (BBT) it showed by difference smaller score from comparator test score. Discussion: It can be concluded that TUGT more appropriate than BBT to predict the falls insident in elderly. Further studies should be consider to used carioca activity model as falls prevention in elderly.